LIVING QUR’AN : KEGIATAN SEMAAN AL QUR’AN JUZ 30 SETIAP AHAD PAGI UNTUK MENINGKATKAN KUALITAS HAFALAN SANTRI - Firda Alfadillah, Zaifa Alifia; Mustofa, Triono Ali (PAI RAFAH, 2023)
Efforts in the process of maintaining memorization of the Qur'an through semaan activities. Apart from maintaining it, it also improves the quality of memorization. Living the Quran as a new method of research/study of social phenomena related to the presence of the Al-Quran in society is of course a breath of fresh air in the academic world. This research uses a qualitative descriptive approach where the data collection process is obtained through direct interviews. The subjects in this research were Ustadz / Ustadzah and students at TPQ Asy Syafaat. The aim of this research is to find out how the process of Semaan activities takes place, the motives and meanings contained in season activities, and the results of Semaan Al Qur'an activities in improving the quality of students' memorization at TPQ Asy Syafaat. The results of this research are the semaan activities carried out every Sunday morning at TPQ Asy Syafaat to train self-confidence, and provide motivation to other students, as evaluation material. The results of the activities of memorizing the Qur'an to improve the quality of memorization at TPQ Asy Syafaat have been successfully implemented.